(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This study aims mainly to measure the effect of credit worthiness of public joint-stock companies listed in the Syrian Securities Commission measured according to the Altman model in reducing earnings management practices. For the purpose of conducting this study, it used Panel Data for 28 companies in the Securities Commission and with midterm observations covering the period from 2012 to 2018. Furthermore, the ARDL model proposed by Pesaran et al (2001) was applied to measure the effect between credit worthiness and earnings management practices. The results of the study showed a statistically significant adverse effect in the long term between the two variables studied under the use of variables (company size, market earnings per share, shareholder profitability) as control variables in the estimated model. Based on the conclusions, a number of recommendations and proposals were presented with the aim of increasing the efficiency of the Syrian shareholding companies and urging the supervisory authorities to activate their role in order to reduce earnings management practices.